'Be a model, not a critic': Self-help culture, implicit censorship and the silent organization. (January 2022) - du Plessis, Erik Mygind
This article seeks to explain 'silent organizations' (i.e. organizations with an absence of critical voices) through an analytical perspective derived from Judith Butler's work on censorship, and in this way suggest an alternative to explanations in the existing literature on employee silence, which are often tied to the actions and motivations of the individual employee. It is thus argued that self-help books are reflective of wider cultural dynamics and concomitant normative pressures directed at the subject in contemporary capitalism, which among other things promote the absence of criticism in the workplace. The empirical point of departure for this argument is the two bestselling and culturally resonant self-help books The Secret by Rhonda Byrne and The 7 Habits of Highly Effective People by Stephen Covey. Theoretically, the article applies Butler's notion of 'implicit censorship' where censorship is understood as productive in the sense of being constitutive of language and subjects. Hence, in the analysis, it is shown how discursive regimes in self-help literature tend to be constructed in such a way that extroverted criticism cannot emerge as a meaningful activity, and is thus implicitly censored.